Implementing improvisation and songwriting to aid the transition to adulthood for adolelescents with special needs : a case study - Tiusanen, Päivi (2016)
Adolescence is a transitional period with many developmental tasks. The adolescents need to resolve the specific question of career choice and establishing authentic friendships. Transition to adulthood is often challenging to the adolescents with special education needs. Research has shown that music can serve as a medium for adolescents’ emotional self-regulation, peer-group affiliation and identity formation. The aim of this case study was to investigate a group music therapy process in which creative music making was utilized. Five adolescents with special education needs participated the sessions during which a group composition was produced. The sessions and the music were recorded and the data was analyzed using a phenomenologically inspired method of microanalysis. The results revealed that a music therapy group process can be beneficial for students with special education needs in transition to adulthood for the purpose of gaining understanding of their responsibilities, their own personal strengths and weaknesses, and about realistic choices.